Drug Smuggling Within Correctional Facilities: Modus Operandi, Regulatory Gaps, and Legal Reform - Purnomo, Hadi; Prasetyo, Edi; Edi Wibowo , Dwi (LITIGASI, 2025)
Drug smuggling in Indonesian correctional institutions remains a complex issue caused by multidimensional factors, hindering the goal of rehabilitation. Despite strict regulations, the involvement of officers and external networks persists. This study aims to identify smuggling modus operandi, assess the impact of weak supervision and officer integrity, and formulate legal solutions. Using a normative juridical method with statute and conceptual approaches, this research reveals that smuggling commonly occurs through family visits, couriers, and illegal communication devices. This study contributes novelty by integrating modus operandi analysis with the gap between legal norms (das sollen) and institutional practice (das sein) in Indonesian correctional law. The findings highlight that current regulations lose effectiveness due to a lack of legal culture and integrity. Consequently, proposed solutions include strengthening internal supervision, enforcing strict sanctions for involved officers, and reforming the correctional legal culture.